Comparison of Learning Effectiveness Using Online and Offline Methods - Muhammad Nail Award; Dedeh Dhohiah; Yeni Andriyani (TOPAZART, 2023)
The Covid-19 pandemic has put the world of education in a very difficult position. On the one hand, students are limited in their movements so as not to contract the virus, on the other hand, students must continue to learn so that there is no lost generation. As a solution, online learning methods are used. Along with the handling of the Covid-19 Pandemic which is considered successful, now the learning method is back using the offline method. However, there are institutions that continue to use online methods because they are considered more effective. This study aims to analyze the effectiveness of online and offline learning methods. The research method used was a survey by taking place at SMP Al Ittihadiyah Ciampea Bogor and a sample of 104 people. Data analysis using difference and percentage tests. The results showed that the achievement of learning targets, understanding of the material, student attendance, and comfort in learning were significantly different between online and offline. As for the presence of teachers and parental encouragement, there is no real difference between online and offline. Thus, offline learning is very effective compared to online learning.